Analisis Unjuk Kerja Oven Pengering Hasil Modifikasi Dengan Variasi Kecepatan Aliran Udara Panas - Muhammat Abdul Fatah, Kemas (P3M Politeknik Negeri Cilacap, 2020)
Cost production efficiency through modified tunnel driyer by using the economizer so that the cost of fuel component eliminated. This study aimed to determine the performance of modified tunnel driyer associated with the quality of the product produced related to achived drying rate . From 3 (three) experiments conducted with variations in the hot air flow velocity of 0.5 m / sec, 0.7 m / sec, and 0.9 m / sec, it was found that only the first experiment occurred condensation and the resulting drying product was declared NG . From the results of the hypothesis independent sample t-test concluded the level of dryness of the results of the 3rd experimental product is better than the results of the 2nd experimental product. Thus, setting a hot air flow rate of 9 m / sec produces the most optimal modified dryer performance.